A study of males with spinal cord injuries in Thailand - Chinchai, Pisak (Curtin University, 2003)
The numbers of people with spinal cord injuries (SCI) in Thailand are increasing. Thai rehabilitation care focuses treatment on acute care with little attention to the lives of clients after discharge from institutions. To date, there has been no research on rehabilitation outcomes and factors relevant to these issues for people with SCI at home and in the community in Thailand. The purpose of this study was to identify and compare the outcomes of functional status, depression, anxiety and stress, and health status of people with SCI, both at discharge and at three months post-discharge from hospital. One hundred twenty-one participants with SCI were recruited from ten major hospitals in Thailand. Data was collected at 48 hours pre-discharge and again at three months post-discharge using the Functional Independence Measure (FIM), the Depression, Anxiety, and Stress Scale (DASS), and the SF-36 Health Survey. The results demonstrated that mean scores of functional status at discharge were significantly higher than at three months post-discharge. Depression and anxiety scores at discharge were significantly lower than depression and anxiety scores at three months postdischarge. Stress score had not significantly changed from discharge to post-discharge. Health status scores at discharge were also higher than at three months post-discharge on eight subscales. Factors relevant to or predicting functional status were marital status, attendant care, number of architectural barriers, fulfilled occupational therapy (OT) needs, and number of different services required but not received. Factors predicting depression, anxiety and stress were marital and economic status, age at onset, education level, duration of disability, fulfilled OT needs, number of different services received, and numbers of different service required but not received.Factors predicting health status were marital status, economic status, age at onset, education level, duration of disability, attendant care, number of architectural barriers, fulfilled OT needs, number of different services received, and number of different services required but not received. Some predictive factors are culture-specific, but on others, rehabilitation professionals could ease the transition from hospital to home for people with SCI.